Transforming wastewater treatment plants in sustainable units coupled with local economies: Microalgae as resource recovery agents. (1st December 2022) - Braga, Matheus Quintão; Magalhães, Iara Barbosa; Silveira, Carolina Ferrari; Couto, Eduardo; Calijuri, Maria Lúcia; Assemany, Paula
Abstract: Besides reducing the sewage organic and nutrient load, microalgae-based wastewater treatments promote the recovery of important natural resources, such as N and P, which can be used for biofuels and animal feed production. In this context, the present study proposes a treatment system based on a circular economy and resource recovery of waste streams: an up-flow anaerobic reactor (UASB, widely used in developing countries such as Brazil) followed by high-rate algae ponds (HRAPs). Geographic Information Systems tools were used to select suitable areas for allocating the proposed system in Minas Gerais (Brazil). Two regions showed excellent suitability for allocating the UASB + HRAP system, with more than 70% coverage each. These areas cover 59 municipalities, with a production capacity of 43, 565 m³/day of raw sewage, a volume that, after treatment, can be used for crop irrigation and fish farming. In addition, municipalities can produce 6621.9 kg/day of microalgae biomass. This biomass can generate 13.96 MWh/day of electrical energy, 1316.7 kg/day of nutrients for animal feed, 3.97 kg of β-carotene, 2576.3 kg of biodiesel, 132.4 kg of Omega-3, 198.7 kg of glycerol or 1125.72 kg of ethanol. Productivities were calculated from three by-product valorization routes of the suggested system: energy, agriculture, and high-value products. The proposed system improves current wastewater treatment standards in the selected regions, with the potential to generate valuable resources compatible with attractive economic activities from these areas. Graphical abstract: Image 1 Highlights: Norte de Minas and Central Mineira have greater suitability for the proposed system. Main resource recovery routes are anaerobic digestion, agriculture and biorefinery. The proposed treatment system can produce energy, animal feed, ethanol and biodiesel. Areas can produce 6621.9 kg day -1 of algal biomass from 43, 565 m³ day-1 of sewage. For animal feed, recovery potential of 1316.67 kg day-1 of algal biomass.